An Analysis of Sustainability Implementation in Malaysian Private Finance Initiative (PFI) Projects: Issues, Challenges and Way Forward - Ismail, kharizam; Khaderi, Shamsida Saidan; Karim, Syed Ahamd Qusoiri Syed Abdul; Talib, Yuhainis Abdul; Salleh, Nor Aini (International Journal of Supply Chain Management, 2019)
Sustainability is a holistic concept whereby covering broad spectrums of aspect social, economic and environmental principles. Private Finance Initiative (PFI) is a long-term approach providing unique opportunity to grasp the issues of sustainability. However, the current implementation of PFI had mistreated to incorporate comprehensive elements of sustainable green development throughout the projects. Thus, the paper intends to investigate the issues, challenges and best practices which significant lead to sustainability performance in Malaysian PFI projects. Employing a focus group method, a brainstorming workshop was conducted involving seventy practitioners and academicians to gather their perceptions on these issues. Data were analysed using thematic analysis. The findings disclosed several key variables of issues and challenges embracing readiness, awareness, policy and documentation, unclear clauses in the concession agreement and Standard of Procedure (SOP) and lack of short–term financial benefits discourages both clients and contractors from embarking on the quest for sustainability development. It is suggested that successful sustainable PFI projects should integrate government support, technology advancement and incentives to both clients and contractors.